Rural Transformation in Northern Thailand: A Study of Common Property Management of “Community” and “Sub-Village Cluster” in Mae Chaem District, Chiang Mai Province from 1957 to 2007 (in Thai) - Noonsong, Anuphab (Asia Social Issues, 2013)
The article aims to study the rural transformation trajectory in the Northern Thailand through the aspect of relationship transformation in the “community” and “sub-village cluster” based on the common property management during 1957 - 2007 under the various context of economic, political and cultural, which led to the transformation of the position and meaning of the rural community in Thailand. The study also illustrate that different sizes and different relationship features between the “community” and the “sub - village cluster” have been significant contribute to the different capacity of common property management. The collapse of the common property management come from several factors included: the unit of relationship is too large, numerous members and the ambiguity of the territory boundaries. These factors cause the control system of the common property reckless. Consequently, the villagers possess the common property. Then the common properties in the sub - village cluster level are collapse lastly, because it is the small unit of relationship, the amount of member is stable and territory is clearer than the community. ความเปลี่ยนแปลงในชนบทภาคเหนือ: ศึกษาการจัดการสมบัติชุมชนของ “ชุมชน” และ “หย่อมบ้าน” อำเภอแม่แจ่ม จังหวัดเชียงใหม่ พ.ศ. 2500 – 2550 บทความมุ่งศึกษาความเปลี่ยนแปลงของ ชนบทภาคเหนือผ่านการศึกษาความเปลี่ยนแปลง ของระบบความสัมพันธ์ภายใน “ชุมชน” และ “หย่อมบ้าน” บนฐานการจัดการสมบัติชุมชน ในช่วง พ.ศ. 2500 - 2550 ภายใต้บริบทต่าง ๆ ทั้ง เศรษฐกิจ การเมือง วัฒนธรรม อันนำมาซึ่งการ เปลี่ยนแปลงสถานภาพและความหมายของ ชุมชนชนบทในสังคมไทย พร้อมกันนั้นต้องการ อธิบายว่าการที่ “ชุมชน” กับ “หย่อมบ้าน” มี ขนาดและระบบความสัมพันธ์ที่แตกต่างกัน ทำให้มีศักยภาพในการจัดการสมบัติชุมชนที่ แตกต่างกัน ความเปลี่ยนแปลงทางเศรษฐกิจและการขยายอำนาจรัฐถาโถมเข้าสู่ชนบท ทำให้การผลิตแบบยังชีพถูกแทนที่ด้วยการผลิตเชิงพาณิชย์ใช้ทุนอย่างเข้มข้น การปรับตัวของพวกเขาคือการยึดครองที่ดินที่เป็นสมบัติชุมชนมาเป็นสมบัติส่วนตัวเพื่อใช้เป็นปัจจัยการผลิต ดังนั้นเมื่อสมบัติชุนที่ทำหน้าที่ร้อยรัดความสัมพันธ์ของคนในชุมชน ถูกทำลายลง ทำให้ไร้พลังเกาะเกี่ยวกันภายใน ในที่สุดความเป็นชุมชนในปัจจุบันไม่มีอีกต่อไป ความเปลี่ยนแปลงที่เกิดขึ้นมีผลทำให้สมบัติชุมชนในระดับ ชุมชนพังทลายลงก่อนเพราะเป็นหน่วยความสัมพันธ์ขนาดใหญ่ มี สมาชิกที่หลากหลายมีอาณาเขตที่ไม่แน่นอนทำให้ระบบการควบคุม หละหลวมจึงถูกชาวบ้านยึดครองเป็นสมบัติส่วนตัวก่อน ขณะที่สมบัติ ชุมชนระดับหย่อมบ้านได้พังทลายลงทีหลังเพราะเป็นหน่วยความสัมพันธ์ขนาดเล็ก มีจำนวนสมาชิกและอาณาเขตที่แน่นอน ทำให้ระบบการควบคุมมีความเข้มข้นมากกว่าในระดับชุมชน